2006
DOI: 10.1063/1.2189928
|View full text |Cite
|
Sign up to set email alerts
|

Improved calculation of the backscattering factor for quantitative analysis by Auger electron spectroscopy

Abstract: Based on a Monte Carlo simulation method, an improved calculation of the backscattering factor in quantitative analysis by Auger electron spectroscopy has been performed by integrating several aspects of recent progresses in the related fields. The calculation used a general definition of backscattering factor, more accurate ionization cross section, up-to-date Monte Carlo model of electron inelastic scattering, and a large number of electron trajectories to ensure less statistical error. The results reveal se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Finally, a number of papers have been published that show significant differences between BCFs from the advanced model and BCFs from the simplified model [9,[11][12][13][14][15][16]. BCFs from the advanced model also can differ from BFs from the Shimizu formulae [4], also based on the simplified model, due to the use of different algorithms and new data for the differential elasticscattering cross sections [17] in recent work that are believed to be more accurate than the data used earlier [18].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a number of papers have been published that show significant differences between BCFs from the advanced model and BCFs from the simplified model [9,[11][12][13][14][15][16]. BCFs from the advanced model also can differ from BFs from the Shimizu formulae [4], also based on the simplified model, due to the use of different algorithms and new data for the differential elasticscattering cross sections [17] in recent work that are believed to be more accurate than the data used earlier [18].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of both, the Si backscattering factor R Si,C for C and that for Ni, R Si,Ni , by about the same amount, ( 14% and 18%, respectively) appears to be consistent and may indicate too high a value from the Ichimura-Shimizu relations. Recent calculations of Jablonski and Powell 7 and of Ding et al 8 show a considerable difference to typical predicted values of Ichimura and Shimizu, which is supported by measurements of Goto (referred to in Ref. 8).…”
Section: Discussionmentioning
confidence: 66%
“…Obviously, r ½ 0 should always be valid. However, new and more detailed calculations by Jablonski and Powell 7 and by Ding et al 8 based on a more general definition of the backscattering factor show that R < 1, i.e. r < 0, is possible for primary energies near the excitation threshold or for glancing incidence angles.…”
Section: Effective Backscattering Factor In Multilayer Depth Profilingmentioning
confidence: 97%
“…The correction for electron-backscattering effects was proposed by Bishop and Riviere [4] in one of the first papers on the formalism for quantitative AES analysis. Recent advances in the theory of electron transport in solids have led to the conclusion that the theoretical model assumed in previous derivations of the formula for the backscattering factor is oversimplified [5][6][7][8][9][10][11]. As a result, BFs calculated from this simplified model are unreliable for low primary energies and/or more-grazing incidence angles.…”
Section: Introductionmentioning
confidence: 94%
“…Recent work has shown that BCFs from the advanced model are a function of the Auger-electron emission angle in addition to other parameters [6][7][8][9][10][11]. As shown above, the BCF also generally depends on the size of the analyzer-acceptance angle.…”
Section: The Nist Bcf Database For Aesmentioning
confidence: 99%